Surface plasma wave in spin-polarized semiconductor quantum plasma. (27th June 2020) - Kumar, Punit; Ahmad, Nafees
Abstract: The possibilities of surface plasma wave (SPW) on a metal-vacuum interface in semiconductor quantum plasma by considering the effects of Coulomb exchange (CE) interaction and the spin-polarization has been explored. The dispersion for the SPW has been setup using the modified quantum hydrodynamic (QHD) model taking into account the Fermi pressure, the quantum Bohm force, the CE, and the electron spin. The optical gain of SPW has been evaluated. It is found that CE effects and spin-polarization increases the wave frequency and enhances the gain during the stimulated emission.